2021
DOI: 10.48550/arxiv.2107.02914
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitative Hilbert irreducibility and almost prime values of polynomial discriminants

Abstract: We study two polynomial counting questions in arithmetic statistics via a combination of Fourier analytic and arithmetic methods. First, we obtain new quantitative forms of Hilbert's Irreducibility Theorem for degree n polynomials f with Galpf q Ď An. We study this both for monic polynomials and non-monic polynomials. Second, we study lower bounds on the number of degree n monic polynomials with almost prime discriminants, as well as the closely related problem of lower bounds on the number of degree n number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…n (H) denotes the number of such polynomials having Galois group not equal to S n , then we may show similarly that E * n (H) = O(H n ) (improving on the previously best known estimate O ǫ (H n+ 1 3 + 8 9n+21 +ǫ ) due to [2]), thus proving van der Waerden's Conjecture also in this non-monic context (that the number of reducible polynomials gives the correct order of magnitude for the count of all polynomials having Galois group not equal to S n ). The analogues of Theorem 2 may be similarly developed for this family as well as for families of polynomials where some of the coefficients a i are fixed.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…n (H) denotes the number of such polynomials having Galois group not equal to S n , then we may show similarly that E * n (H) = O(H n ) (improving on the previously best known estimate O ǫ (H n+ 1 3 + 8 9n+21 +ǫ ) due to [2]), thus proving van der Waerden's Conjecture also in this non-monic context (that the number of reducible polynomials gives the correct order of magnitude for the count of all polynomials having Galois group not equal to S n ). The analogues of Theorem 2 may be similarly developed for this family as well as for families of polynomials where some of the coefficients a i are fixed.…”
Section: Introductionsupporting
confidence: 63%
“…Zywina [47] (2010), who refined this to E n (H) = O(H n−1/2 ) for large n; Dietmann [14] (2012), who proved using resolvent polynomials and the determinant method that E n (H) = O(H n−2+ √ 2 ); and Anderson, Gafni, Lemke Oliver, Lowry-Duda, Shakan, and Zhang [2] (2021) who prove that E n (H) = O(H n− 2 3 + 2 3n+3 +ǫ ). For n ≤ 4, van der Waerden's conjectured optimal upper bound of O(H n−1 ) was proven by Chow and Dietmann [10].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, van der Waerden showed that among the ∼ (2𝐻) 𝑛 monic integral polynomials of degree 𝑛 whose coefficients are bounded in absolute value by 𝐻, at most 𝑂(𝐻 𝑛−6∕((𝑛−2) log log 𝑛) ) have associated Galois group not 𝑆 𝑛 . This was subsequently improved by Gallagher [14] to 𝑂(𝐻 𝑛−1∕2 log 𝐻), by Zywina [28] to 𝑂(𝐻 𝑛−1∕2 ), by Dietmann [12] to 𝑂(𝐻 𝑛−2+ √ 2+𝜀 ), by Anderson, Gafni, Lemke Oliver, Lowry-Duda, Shakan, and Zhang [1] to 𝑂(𝐻 𝑛− 2 3 + 2 3𝑛+3 +𝜀 ), and most recently to the optimal 𝑂(𝐻 𝑛−1 ) in [3].…”
Section: Estimates On Reducibilitymentioning
confidence: 99%
“…The invariant was constructed in terms of the discriminant of a certain canonical but irrational positive-definite SL 2 (ℝ)-covariant binary quadratic form 𝑄 of 𝑓. More precisely, consider a binary 𝑛-ic form 𝑓 with coefficients as in (1). If 𝑎 0 ≠ 0, we may write 𝑓(𝑥, 𝑦) = 𝑎 0 (𝑥 − 𝛼 1 𝑦)(𝑥 − 𝛼 2 𝑦) ⋯ (𝑥 − 𝛼 𝑛 𝑦) with 𝛼 𝑖 ∈ ℂ, and then, for any vector 𝑡 = (𝑡 1 , … , 𝑡 𝑛 ) of positive real numbers, we may consider the positive-definite quadratic form 𝑄 𝑡 (𝑥, 𝑦) = 𝑛 ∑ 𝑗=1 𝑡 2 𝑗 (𝑥 − 𝛼 𝑗 𝑦)(𝑥 − 𝛼 𝑗 𝑦).…”
mentioning
confidence: 99%